Effects of soil management of emergence of annual weeds - Blanco, Hélio García; Blanco, Flavio Martins Garcia (Pesquisa Agropecuaria Brasileira, 1991)
Through montly samplings, in the period of October to April, the emergence dinamics of 10 weed plants was determined under two forms of treatment: destruction of the former flora by land stiring with rotary harrow pulled by micro tractor, or, no stiring with the use of contact herbicide. The results showed that cultivation management favored the emergence of the species Bidens pilosa, Amaranthus viridis, Sonchus oleraceus, Rhynchelitrum roseum, Portulaca oleracea, Eleusine indica, Acanthospermum hispidum, Galinsoga paviflora and Eragrostis pilosa. The emergence dinamics of Brachiaria plantaginea was not influenced by soil management. The initial emergence in October, in a disturbed soil, ment 85 to 95% of the total emergence for B. pilosa, A. viridis and S. oleraceus. For R. roseum, G. paviflora, P. oleracea and A. hispidum the first emergence expresses 80, 70, 65 and 50% of the total, respectively.